Development of Hesitant Fuzzy-Based Project Selection Method with Consideration of Benefits, Opportunities, Costs and Risks - Karina Ayu Trijana; Udisubakti Ciptomulyono (IPTEK Journal of Proceedings Series, 2020)
PT X, a power generation company, hasn’t been able to meet their target in the business development segment over the past few years. This is due to a problem detected in their Project Portfolio Management, in which PT X’s project selection method hasn’t considered the ambiguity nature of project’s information and risks. This study is going to develop a project selection method for PT X using MCDM (multi criteria decision making) with BOCR (benefit, opportunity, cost, risk) Concept to evaluate many criteria that need to be considered by the company, especially conflicting criteria such as benefit with cost and opportunity with risk. Not only that, hesitant fuzzy will be used because project itself has many uncertain or ambiguous information, so stakeholder will face difficulties in determining the value for the evaluation. From the integration of those things in this study, it is found that for PT X, Benefit has the biggest priority, followed by Opportunity, Risk, and Cost in Project Selection for PT X. It is also found that based on additive-BOCR, Project C gives the optimal value for PT X, followed by Project B, Project A, Project D, dan Project E.